2011
DOI: 10.1007/s12640-011-9254-y
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuroprotective peptide exerting protective effects in neuronal injuries. We have provided evidence that PACAP is neuroprotective in several models of retinal degeneration in vivo. Our previous studies showed that PACAP treatment ameliorated the damaging effects of chronic hypoperfusion modeled by permanent bilateral carotid artery occlusion. We have also demonstrated in earlier studies that treatment with PACAP antagonists further aggravates reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 81 publications
4
38
0
Order By: Relevance
“…pacap deficient mice displayed larger infarcted area in a model of focal cerebral ischemia and the extent of the ischemic retinal lesion was also increased [43]. there are similar findings in peripheral tissues in ischemic lesions.…”
Section: The Effect Of Endogenous Pacap In Ischemia/reperfusion-inducsupporting
confidence: 62%
“…pacap deficient mice displayed larger infarcted area in a model of focal cerebral ischemia and the extent of the ischemic retinal lesion was also increased [43]. there are similar findings in peripheral tissues in ischemic lesions.…”
Section: The Effect Of Endogenous Pacap In Ischemia/reperfusion-inducsupporting
confidence: 62%
“…Exogenous PACAP administration could partially protect against this retinal degeneration in the KO mice. These results clearly show that endogenous PACAP reacts as a stress-response peptide that is necessary for endogenous protection against different retinal insults [ 106 ].…”
Section: Studies In Pacap and Receptor Gene Modifi Ed Animalsmentioning
confidence: 61%
“…Ohtaki and coworkers showed that PACAP KO mice have increased infarct volume in a model of stroke [ 60 ] with increased edema formation [ 61 ]. Similar results were obtained in the retina: in bilateral carotid artery occlusioninduced retinal ischemia PACAP KO mice showed increased tissue damage [ 62 ]. In peripheral organ ischemia, it has been shown that PACAP KO mice react with increased tissue injury in ischemia-reperfusion-induced kidney lesion [ 27 , 63 ].…”
Section: Small Intestinal Ischemic Injury In Pacap Knockout (Ko) Micementioning
confidence: 67%